Pengaruh Capital Intensity, Pertumbuhan Penjualan, dan Kepemilikan Institusional terhadap Penghindaran Pajak Pada Perusahaan Sektor Consumer Non-Cyclicals Yang Terdaftar di BEI Tahun (2018-2022) - Rahma, Intan; Jelanti, Desi; W.A, Sri Putri Winingrum (Jurnal Ekonomi dan Bisnis, 2025)
At present, the main pillar in the State Budget (APBN) comes from taxes to support the implementation of national development projects and improve people's welfare in various aspects of life. This study aims to determine the effect of Capital Intensity, Sales Growth, and Institutional Ownership on Tax Avoidance in Consumer Non-Cyclicals sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period. With a quantitative approach, this study uses 33 company samples selected through a purposive sampling method. Research data were obtained from annual financial reports and analyzed using Eviews 9 software. The results of the study indicate that simultaneously Capital Intensity, Sales Growth, and Institutional Ownership have an effect on Tax Avoidance. Partially, Capital Intensity and Sales Growth have a significant effect on Tax Avoidance, while Institutional Ownership has no effect. These findings provide practical implications for companies, governments, and other stakeholders to understand the factors that influence tax avoidance behavior.